The 2014–2015 eruption of Fogo volcano: Geodetic modeling of Sentinel‐1 TOPS interferometry. Issue 21 (6th November 2015) - González, Pablo J.; Bagnardi, Marco; Hooper, Andrew J.; Larsen, Yngvar; Marinkovic, Petar; Samsonov, Sergey V.; Wright, Tim J.
Abstract: After 20 years of quiescence, Fogo volcano erupted in November 2014. The eruption produced fast‐moving lava flows that traveled for several kilometers and destroyed two villages. This event represents the first episode of significant surface deformation imaged by the new European Space Agency's Sentinel‐1 satellite in its standard acquisition mode, Terrain Observation by Progressive Scans (TOPS), which differs from that of previous synthetic aperture radar (SAR) missions. We perform a Bayesian inversion of Sentinel‐1 TOPS SAR interferograms spanning the eruption and accurately account for variations in the TOPS line‐of‐sight vector when modeling displacements. Our results show that magma ascended beneath the Pico do Fogo cone and then moved laterally toward its southwestern flank, where the eruptive fissure opened. This study provides important insights into the inner workings of Fogo volcano and shows the potential of Sentinel‐1 TOPS interferometry for geophysical (e.g., volcano monitoring) applications. Key Points: The 2014–2015 Fogo eruption is first event imaged with Sentinel‐1 TOPS Eruption was fed by a single but complex dike Surface deformation modeling of Sentinel‐1 TOPS‐mode InSAR data